Posterolateral intertransverse lumbar arthrodesis in the New Zealand white rabbit model: The illustration of an alternative surgical approach - Buyong, Zunariah; Zakaria@Mohamad, Zamzuri; Che Seman, Che Nor Zarida; Abdul Jalil, Rosnani (The Faculty of Medicine, International Islamic University Malaysia, 2012)
Introduction: The New Zealand White (NZW) rabbit model is commonly used for the research of posterolateral intertransverse lumbar arthrodesis. The standard approach reported by many researchers are a muscle splitting approach through the intermuscular plane between multifidus and longissimus muscles. Methods: In this research the fusion bed was exposed by retracting the three groups of paraspinal muscles (multifidus, longissimus and iliocostalis) medially. Results: This alternative method showed good exposure of the transverse processes and intertransverse membrane with less bleeding from the muscles observed. No death due to surgical complication was observed out of twenty-four rabbits operated. Conclusion: An easy and safe method for performing posterolateral intertransverse lumbar arthrodesis was demonstrated and recommended as an alternative approach for surgery on New Zealand White rabbits.